Dietary mannan oligosaccharides strengthens intestinal immune barrier function via multipath cooperation during Aeromonas Hydrophila infection in grass carp (Ctenopharyngodon Idella) - Lu, Zhi-Yuan; Feng, Lin; Jiang, Wei-Dan; Wu, Pei; Liu, Yang; Jiang, Jun; Kuang, Sheng-Yao; Tang, Ling; Li, Shu-Wei; Zhong, Cheng-Bo; Zhou, Xiao-Qiu (Frontiers in Immunology, 2022)
In recent years, mannose oligosaccharide (MOS) as a functional additive is widely used in aquaculture, to enhance fish immunity. An evaluation of the effect of dietary MOS supplementation on the immune barrier function and related signaling molecules mechanism of grass carp (Ctenopharyngodon idella) was undertaken in the present study. Six diets with graded amounts of MOS supplementation (0, 200, 400, 600, 800, and 1000 mg/kg) were fed to 540 grass carp over 60 days. To examine the immune response and potential mechanisms of MOS supplementation on the intestine, a challenge test was conducted using injections of Aeromonas hydrophila for 14 days. Results of the study on the optimal supplementation with MOS were found as follows (1) MOS enhances immunity partly related to increasing antibacterial substances content and antimicrobial peptides expression; (2) MOS attenuates inflammatory response partly related to regulating the dynamic balance of intestinal inflammatory cytokines; (3) MOS regulates immune barrier function may partly be related to modulating TLRs/MyD88/NFκB and TOR/S6K1/4EBP signalling pathways. Finally, the current study concluded that MOS supplementation could improve fish intestinal immune barrier function under Aeromonas hydrophila infected conditions.